The 7th 2014 Biomedical Engineering International Conference 2014
DOI: 10.1109/bmeicon.2014.7017432
|View full text |Cite
|
Sign up to set email alerts
|

The red and blue rooms affect to brain activity, cardiovascular activity, emotion and saliva hormone in women

Abstract: The color and light have effect on physiology, psychology, cognitive performance and hormone production in the human. In this paper, we aim to study red and blue color with their effect on brain activity, cardiovascular activity, emotion and saliva hormone. Each participant was testing in red and blue room. Participant was measure the EEG, ECG, SpOz, pulse rate, saliva hormone (melatonin, cortisol, testosterone, progesterone, estradiol and DHEAS), and emotion. The results showed that red room regulates the ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…On the one hand, several studies have investigated the influence of color of light on human physiology throught biochemical markers such as cortisol [ 2 , 3 ] or melatonin [ 2 4 ] level, and bio-signals such as electrocardiographic (ECG) [ 3 , 4 ] or electroencephalographic (EEG) [ 3 , 5 11 ] signals. In this sense, only a few colors have been investigated and blue is in most of the studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, several studies have investigated the influence of color of light on human physiology throught biochemical markers such as cortisol [ 2 , 3 ] or melatonin [ 2 4 ] level, and bio-signals such as electrocardiographic (ECG) [ 3 , 4 ] or electroencephalographic (EEG) [ 3 , 5 11 ] signals. In this sense, only a few colors have been investigated and blue is in most of the studies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that early EEG responses (e.g., event-related potentials during the first milliseconds) depend on their adaptation to different colors of light [ 11 ]. Another recent and preliminary work showed that a short stay (20 minutes) inside a blue room caused cortisol level reduction in a woman [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also blue had no influence on HS, but it showed fearreducing effects in the within-group comparison. This is interesting from the fact that normally the color blue increases the production of progesterone (Figueiro & Rea, 2010;Sroykham & Wongsawat, 2014). Also, an increase of progesterone is related to a decrease of FF (Ball et al, 2014), so there could be a potential connection between colors, hormones and implicit motives.…”
Section: Discussionmentioning
confidence: 96%
“…Research from medicine and photobiology indicates that colors are related to expressions of hormones, which also are important in the health context. The color red is related to the expression of cortisol and testosterone, and the color blue to salvia DHEAS and progesterone (Figueiro & Rea, 2010;Sroykham & Wongsawat, 2014). As green is negatively associated with inflammation and cortisol but positively with melatonin, it is used for phototherapy in newborn (Vecchi, Donzelli, Migliorini, & Sbrana, 1983;Horne, Donlon & Arendt 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the color of light, specifically blue light, has been shown to aid in post-stress recovery (Minguillon et al, 2017). Light has also been shown to effect comfort (Küller and Wetterberg, 1993) as well as brain activity, cardiovascular activity and even emotional states (Sroykham, 2015). Stone (1992) demonstrated that poor lighting can cause headaches and patient discomfort.…”
Section: Lightingmentioning
confidence: 99%